Emergency response and recovery management in the 2023 Turkey earthquake: Lessons learned from AFAD's systematic approach and international EMT coordination - Rahman, Safrizal; Anugerah, Panji; Mubarak, Muhammad Iqbal EL; Atayoğlu, Ali Timuçin (Svāsthya: Trends in General Medicine and Public Health, 2025)
The February 6, 2023, earthquake in Turkey (7.8 Mw) created unprecedented challenges for emergency response systems.  This study examines Turkey's Disaster and Emergency Management Authority's (AFAD) systematic approach and coordination with international emergency medical teams (EMTs), with a particular focus on the contributions of the Indonesian Aceh EMT.  This intrinsic descriptive case study employed qualitative methodologies, including in-depth interviews with 20 participants involved in humanitarian response. Document analyses of AFAD, WHO, and UN OCHA reports complemented primary data collection. Purposive sampling ensured that the participants had relevant disaster response experience. The data were subjected to thematic analysis via NVivo software to identify recurring patterns. AFAD demonstrated preparedness through comprehensive disaster response frameworks, mobilizing over 300,000 volunteers despite initial delays in some cases. GIS mapping technology facilitated the real-time identification of affected regions, reducing response times by 25%. The Indonesian Aceh EMTs arrived on day nine and provided medical services to more than 5,000 individuals within their first operational week. More than 100,000 displaced individuals received immediate aid within 48 h of the earthquake through the AFAD's prepositioning of medical supplies. Response effectiveness is influenced by several factors, including technological integration, volunteer mobilization, and international coordination.  The 2023 Turkey earthquake underscores the importance of systematic preparedness and international collaboration in disaster management in Turkey. Recommendations include improving logistical systems for rapid deployment, increasing the utilization of advanced technologies, enhancing multilingual training, and continuously evaluating disaster management frameworks.